The Effect of Work Discipline and Work Motivation Towards Employee Performance at PT. Alamjaya Wirasentosa - Salim, Nico; Amelia, Amelia (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
In every company, human resource plays an important role in the company growth to achieve certain goals. Having a qualified and a skillful employee will also help the company to achieve their goals easily. Employee performance could be influence by many factors, which is Work Discipline and Work Motivation. The purpose of this research is to find out the effect of work discipline and work motivation towards employee performance at PT. Alamjaya Wirasentosa. The data that are going to be used in this research is conducted through an interviews and questionnaire which the employees will answer all of the questions. As the population of this study is 80 employees of PT. Alamjaya Wirasentosa. The data analysis method that are being used in this research are descriptive statistic test, analysis descriptive test, classical assumption test, and multiple linear regression test. The final output of this research shows that there is only one hypothesis is being accepted, which is Work Discipline has significant influence towards Employee Performance. While another hypothesis is being rejected, which is Work Motivation has no significant influence towards Employee Performance.